Active Music Therapy Following Acute Stroke: A Single-Arm Repeated Measures Study. (5th November 2021) - Rushing, Jessica; Capilouto, Gilson; Dressler, Emily V; Gooding, Lori F; Lee, Jessica; Olson, Anne
Abstract: Experiencing a stroke can lead to difficulties with emotion regulation and mood disorders like depression. It is well documented that poststroke depression (PSD) affects a third of all stroke survivors. Higher levels of depression and depressive symptoms are associated with less efficient use of rehabilitation services, poor functional outcomes, negative impacts on social participation, and increased mortality. Mood in the acute phases of stroke recovery may be a key factor influencing the depression trajectory with early depression predicting poor longitudinal outcomes. The purpose of the study was to examine the effect of one active music therapy (AMT) treatment on mood following a first-time ischemic stroke during acute hospitalization. Forty-four adults received AMT defined as music-making interventions that elicit and encourage active participation. The Faces Scale was used to assess mood immediately prior to and following the treatment. A significant change in mood was found following one treatment. Comment analysis indicated that participants viewed music therapy as a positive experience. Findings here support the use of brief AMT to provide early psychological support to stroke survivors. Continued investigation into the role of music therapy in early stroke recovery is recommended.